The Effect of Service Quality on Patient's Family Satisfaction in the Nicu Care of the Public Hospital in Datu Beru Takengon Region - Kusnatalia Kusnatalia; Arifah Devi Fitriani; Asriwati Amirah (Journal La Medihealtico, 2020)
The World Health Organization (WHO) infant mortality rate is the first indicator in determining a child's health status, 3.6 million of the 120 million newborns experience asphyxia, and nearly 1 million babies die. Meanwhile, the prevalence of patients treated at the NICU at the Datu Beru Takengon Hospital from 2016 to 2019 continues to decline every year. The purpose of this study was to determine and analyze the effect of technical competence, efficiency and patient safety on patient family satisfaction. The research design used an analytic survey with a cross-sectional design. The data that had been collected were processed using univariate and bivariate and multivariate analysis. The population of all parents of babies who were treated in the NICU Care Room at Datu Beru Takengon Hospital was 329 people. The sampling technique used accidental sampling. The number of samples that will be studied is 67 people. The results of the research on technical competence variables obtained p-value = 0,000, efficiency 0,000, and patient safety 0,000 <α 0.05, meaning that there is an influence between technical competence, efficiency and patient safety on family satisfaction, from the results of multivariate analysis, the most influential variables are found. in this study is the technical competency variable with an Exp B value of 1.003. The conclusion is that there is an influence between technical competence, efficiency and patient safety while the multivariate analysis shows that the most dominant factor is the variable of technical competence on family satisfaction. It is recommended that the hospital be able to improve the technical competence of nurses in the NICU room by holding training and workshops both internal and external training.